Determinacion de las formulas de volumen de las trozas de Pinus Caribaea Morelet var. Caribaea - Garcia Delgado, J.M.=700 1 Gonzalez Hernandez, O.; Leon sanchez, M.A.; Henry Torriente, P.P.
(Es, En)
Ilus., 18 ref.
Keywords: PINUS CARIBAEA; MODELOS MATEMATICOS; VOLUMEN; TROZAS; CUBA; FORMULA DE VOLUMEN; REVISTA FORESTAL BARACOA